The Extent of E-training Elements Availability: An applied study to Saudi Aramco – Abha - Alzahrani, Daifallah Ahmad; Alammar, Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
The current research aimed to identify the availability of e-training elements in Saudi Aramco in the city of Abha, and to use the descriptive analytical approach. The questionnaire was adopted as a tool to collect information. The research population was represented in all employees of Saudi Aramco in the city of Abha who numbered (270) employees. A random sample consisting of (130) employees was selected. The findings of the research concluded that the internal and external elements of e-training are extremely available in Saudi Aramco in Abha, and there are statistically significant differences about the availability of e-training elements in Saudi Aramco in Abha due to the variable (age, years of service), While there are no statistically significant differences attributable to the variable (gender, academic qualification, career position). The research proposed a set of recommendations, the most important of which is the necessity of working on the sustainability of achieving the elements of e-training for employees of Saudi Aramco in Abha, and the need to preserve all elements of e-training related to elements of training (trainer, trainee, training environment, training material).